Using mice to model Alzheimer's dementia: an overview of the clinical disease and the preclinical behavioral changes in 10 mouse models - Webster, Scott J.; Bachstetter, Adam D.; Nelson, Peter T.; Schmitt, Frederick A.; Van Eldik, Linda J. (Frontiers in Genetics, 2014)
The goal of this review is to discuss how behavioral tests in mice relate to the pathological and neuropsychological features seen in human Alzheimer’s disease (AD), and present a comprehensive analysis of the temporal progression of behavioral impairments in commonly used AD mouse models that contain mutations in amyloid precursor protein. We provide a brief overview of neuropathological changes seen in AD brain, and some of the clinical neuropsychological assessments used to measure cognitive deficits. This is followed by a critical assessment of behavioral tasks that are used in AD mice to model the cognitive changes seen in humans. Behavioral tests discussed include spatial memory tests (Morris water maze, radial arm water maze, Barnes maze), associative learning tasks (passive avoidance, fear conditioning), alternation tasks (Y-Maze/T-Maze), recognition memory tasks (Novel Object Recognition), attentional tasks (3 & 5 choice serial reaction time), set-shifting tasks, and reversal learning tasks. We discuss the strengths and weaknesses of each of these tests, and how they may correlate with clinical assessments in humans. Finally, the temporal progression of both cognitive and non-cognitive deficits in ten AD mouse models (PDAPP, TG2576, APP23, TgCRND8, J20, APP/PS1, TG2576 + PS1(M146L), APP/PS1 KI, 5xFAD and 3xTg-AD) are discussed. Mouse models of AD and the behavioral tasks used in conjunction with those models are immensely important in contributing to our knowledge of disease progression, and are useful tools to study AD pathophysiology and the resulting cognitive deficits. However, investigators need to be aware of the potential weaknesses of the available preclinical models in terms of their ability to model cognitive changes observed in human AD. It is our hope that this review will assist investigators in selecting an appropriate mouse model, and accompanying behavioral paradigms to investigate different aspects of AD pathology and disease progression.